Pengaruh Ketersediaan Modal, Latar Belakang Pendidikan dan Lingkungan Terhadap Keputusan Berwirausaha UMKM di Kota Malang - Ridwan, Muhammad; Rizal, Mohammad; Hardaningtyas, Ratna Tri (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to determine and assess the influence of capital availability, educational background and environment on entrepreneurial decisions, both partially and simultaneously. The method used in this research is quantitative. The population in this study were MSMEs in Malang City using 100 samples. In this research, questionnaires were used as a data collection method. The results of this research show that 1) Availability of capital has a significant influence on MSME entrepreneurial decisions in Malang City. 2) Educational background has a significant influence on MSME entrepreneurial decisions in Malang City. 3) The environment has a significant influence on MSME entrepreneurial decisions in Malang City. 4) Availability of capital, educational background and environment simultaneously influence MSME entrepreneurial decisions in Malang City. Keywords: Availability of Capital, Educational Background, Environment, Entrepreneurial Decisions.